Hematopoietic Stem Cell Function in a Murine Model of Sickle Cell Disease - Elisabeth H. Javazon; Mohamed Radhi; Bagirath Gangadharan; Jennifer Perry; David R. Archer (Anemia)
Previous studies have shown that the sickle environment is highly enriched for reactive oxygen species (ROS). We examined the oxidative effects of sickle cell disease on hematopoietic stem cell function in a sickle mouse model. In vitro colony-forming assays showed a significant decrease in progenitor colony formation derived from sickle compared to control bone marrow (BM). Sickle BM possessed a significant decrease in the KSL (c-kit+, Sca-1+, Lineage−) progenitor population, and cell cycle analysis showed that there were fewer KSL cells in the G0 phase of the cell cycle compared to controls. We found a significant increase in both lipid peroxidation and ROS in sickle-derived KSL cells. In vivo analysis demonstrated that normal bone marrow cells engraft with increased frequency into sickle mice compared to control mice. Hematopoietic progenitor cells derived from sickle mice, however, demonstrated significant impairment in engraftment potential. We observed partial restoration of engraftment by n-acetyl cysteine (NAC) treatment of KSL cells prior to transplantation. Increased intracellular ROS and lipid peroxidation combined with improvement in engraftment following NAC treatment suggests that an altered redox environment in sickle mice affects hematopoietic progenitor and stem cell function.